2021
DOI: 10.3390/machines9040078
|View full text |Cite
|
Sign up to set email alerts
|

Cybersecurity Risk Assessment in Smart City Infrastructures

Abstract: The article is devoted to cybersecurity risk assessment of the dynamic device-to-device networks of a smart city. Analysis of the modern security threats at the IoT/IIoT, VANET, and WSN inter-device infrastructures demonstrates that the main concern is a set of network security threats targeted at the functional sustainability of smart urban infrastructure, the most common use case of smart networks. As a result of our study, systematization of the existing cybersecurity risk assessment methods has been provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 32 publications
0
17
0
2
Order By: Relevance
“…In Table 4 there are functions that an enterprise must have, they are marked with the letter M. The lack of such features means that customers go somewhere to the competition [75]. It can be concluded that the respondents understand the need for sustainable development [76], and the so-called the related features were treated by them mainly as indispensable features, i.e., they must be among the attributes of corporate social media [77,78]. Comparing the results of these studies with previous studies available in the literature, it was possible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 4 there are functions that an enterprise must have, they are marked with the letter M. The lack of such features means that customers go somewhere to the competition [75]. It can be concluded that the respondents understand the need for sustainable development [76], and the so-called the related features were treated by them mainly as indispensable features, i.e., they must be among the attributes of corporate social media [77,78]. Comparing the results of these studies with previous studies available in the literature, it was possible.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of smart city activities, individual dimensions of activities have specific advantages and disadvantages. Smart solutions provide long-term benefits, ensure a balance between the availability of modern intelligent solutions and the sense of security among residents, the sense of privacy and freedom cannot be disturbed [78][79][80][81].…”
Section: Discussionmentioning
confidence: 99%
“…Iz tog razloga uvedena je mera povrata investicija u bezbednost (Return on Security Investment, ROSI) za kvantifikaciju gubitaka koji su izbegnuti zahvaljujući preventivnim ulaganjima u bezbednost [11]. Kvantitativni metodi za procenu rizika mogu se klasifikovati u tri osnovne kategorije: (1) analitički metodi kao što su: analiza osetljivosti, analiza scenarija, metod diskontnih stopa prilagođenih riziku; (2) probabilistički teorijski metodi koji se zasnivaju na simulaciji, teoriji igara ili konstrukciji stabla, i (3) nekonvencionalni metodi, među kojima su najpoznatiji metodi zasnovani na fazi logici ili na mašinskom učenju [12]. Hibridni metodi kombinuju prethodno opisane pristupe, na primer, stručnu procenu sa nekim od kvantitativnih metoda [13], [14].…”
Section: Slika 1 Ilustracija Procesa Procene Bezbednosnog Rizika U Icsunclassified
“…U [28] je prikazan pristup za dinamičku procenu bezbednosnog rizika u ICS, zasnovan na Bajesovoj mreži sa fazi verovatnoćama, koji je verifikovan na primeru simulacije upravljanja hemijskim reaktorom. Kvantitativni metod za procenu sajber bezbednosnog rizika u infrastrukturi pametnih gradova, zasnovan na ANN pristupu, opisan je u [12].…”
Section: Metodi Zasnovani Na Mašinskom Učenjuunclassified
“…On the other hand, the strategy of digitizing the circularity of urban metabolism through real-time monitoring stations of water and energy consumption, GPS tracking sensors and digital cameras to control and manage mobility, cloud computing platforms for sharing sensitive data and information between agencies, departments, divisions, utilities, etc., outlines a multitude of challenges and criticalities related to: (a) the quality of the data used [75]; (b) the degree of traditional and cyber security [76]; (c) the necessary integration of data and information of different types, provided by a wide range of stakeholders [77], and (d) the ability of policymakers, urban managers and planners to convert continuous and real-time feedback from stakeholders into forward-looking urban circularity strategies [11].…”
Section: Introductionmentioning
confidence: 99%